Variation in somatic symptoms by patient health questionnaire-9 depression scores in a representative Japanese sample - Eri Hoshino; Sachiko Ohde; Mahbubur Rahman; Osamu Takahashi; Tsuguya Fukui; Gautam A. Deshpande (BMC, 2018)
Abstract Background This study aims to evaluate variation in somatic symptoms by age using patient health questionnaire-9 (PHQ) depression scores, which may be helpful in identifying depression. Methods The study evaluated a nationally representative cross-sectional sample of community-dwelling adults in Japan in 2013. We utilized the PHQ to identify risk for depression, with PHQ ≥ 10 defining at least moderate depression. Bivariate and factor analyses were used to capture underlying patterns in self-reported symptoms over a 30 day period; aged-stratified multivariate logistic regression was performed to further explore associations between age, symptoms, and depression. Results Of 3753 respondents, 296 (8, 95% CI 7.0-8.8) reported a PHQ ≥ 10; 42% of these were male and mean age was 51.7 years old (SD = 18.6). Multivariate analysis showed that presence of fatigue and malaise (OR = 1.7, 95% CI 1.3-2.4) was significantly associated with PHQ ≥ 10. After stratification by age, PHQ ≥ 10 was associated with gastrointestinal complaints among 18-39 year olds (OR = 1.7, 95% CI 1.0-2.9); fatigue and malaise (OR = 1.8, 95% CI 1.1-3.1) among 40-64 year olds; and fatigue and malaise (OR = 1.8, 95% CI 1.1-3.0) as well as extremity pain (OR = 1.7, 95% CI 1.0-2.8) in over 65 year olds. Conclusion Age-related somatic symptom correlates of PHQ ≥ 10 differ across the lifespan. Predominantly gastrointestinal symptoms in younger patients, and generalized fatigue, malaise, and musculoskeletal pain in older groups were observed. In order for screening physicians to proactively identify depression, awareness of age-related somatic symptoms is warranted.